APPLICATIONS OF MACHINE LEARNING IN DIAGNOSTICS AND SPECIAL EDUCATION INTERVENTIONS - Alim Hardiansyah; Ardiyanto Saleh Modjo; Arnes Yuli Vandika (Indonesian Journal of Education (INJOE), 2023)
Special education is a basic right for children with special needs. In the technological era, machine learning plays an important role in supporting the education of these children by providing personalized learning, early detection of disorders, assisting communication, and training life skills. With joint efforts, we can create special educational environments that support optimal development for all children, including those with special needs. The importance of special education cannot be ignored and machine learning is emerging as a powerful ally in providing an approach tailored to the needs of each child. Machine Learning can customize curriculum, monitor progress, and provide real-time feedback. This helps create a more personalized and effective learning experience. The literature study approach was used to conduct the research. Data and information about the use of machine learning in special education diagnosis and interventions were gathered through a review of the literature. The concept of special education, issues with diagnosis and intervention in special education, the use of technology in education, the introduction and application of machine learning in the field of education, and the advantages and difficulties of implementing machine learning in special education are all covered in this research